Dual Behavioral—Physiological Buffering of Mothers' Milk Facilitates Drought Adaptability of Pastoralists and Agropastoralists in Northern Kenya - Fujita, M.; Wander, K.; Straight, B.; Wamwere-Njoroge, George J. (2025)
Background Mothers physiologically buffer key milk nutrient content against nutritional stress. How this is nested in upstream behavioral buffering is not well understood.